Pelatihan Aplikasi Comic Page Creator Sebagai Media Pembelajaran Inovatif bagi Guru di Kota Medan - Alfitriani Siregar; Resty Wahyuni; Ratna Sari Dewi (Jurnal Pengabdian UNDIKMA, 2023)
This community service aims to enhance teaching abilities by using mobile learning-based comic page maker applications as creative learning media. The execution of this service required planning, implementation, and assessment phases of training. Fourteen instructors from Madrasah Tsanawiyah in Medan participated in this service activity. The evaluation instrument used survey percentages and was analyzed descriptively. This service showed that 71% of teachers understood and could use the mobile learning-based comic page creator application in class. In addition, teachers were enthusiastic about exploring innovative skills and became creative using mobile/mobile applications. By mastering this application, the teacher can convey teaching material more concisely through pictures and text so that learning objectives are conveyed properly to students.